Congenital Middle Ear Cholesteatoma: Experience from 26 Surgical Cases. (May 2013) - Yamatodani, Takashi; Mizuta, Kunihiro; Hosokawa, Kumiko; Takizawa, Yoshinori; Sugiyama, Kenichi; Nakanishi, Hiroshi; Mineta, Hiroyuki
Objectives: We analyzed the clinical features and surgical techniques used in cases of childhood congenital cholesteatoma of the middle ear. Methods: We studied 26 patients (26 ears) who underwent surgery for congenital cholesteatoma between January 1998 and December 2009, focusing on the location and type of cholesteatoma, the surgical procedures involved, and the results obtained. Patients with prior otologic procedures were excluded. A 4-stage system was used to grade the cholesteatomas. Results: The frequency of posterior-quadrant involvement and open-type cholesteatomas increased in the more advanced stages. Second-look operations were performed in 60% of stage III and 75% of stage IV cases; and residual cholesteatomas were found in 20% of stage III and 75% of stage IV cases. Of the cases evaluated both before and after the operation, 100% of stage I and II cases, 86% of stage III cases, and 50% of stage IV cases showed improvement in hearing function. Conclusions: The staging system is relatively simple, while accurately reflecting clinical results. However, there are many differences between the anterior and posterior types of congenital cholesteatomas in surgical approach and postoperative progression that are not reflected in the classification systems and require further study. In addition, we reviewed the surgical procedures involved in anterior-quadrant cases, and propose a modified surgical procedure.